Pablo Melogno and Thomas Kuhn - Hoyningen-Huene, Paul (Estudios de Filosofía, 2025)
This paper discusses seven of Melogno’s papers on Kuhn from 2019 to 2024. It analyzes Melogno’s arguments about the relationship between Kuhn’s early and late historiography, his rejection of the discovery-justification distinction, and his move towards questions of meaning and semantics in the 1980s. This paper argues that Melogno made vital contributions to “Kuhn studies,” carefully tracing developments in Kuhn’s thought over time. However, it also engages critically with some of Melogno’s central claims, like his argument that The Structure of Scientific Revolutions represented a sharp break from Kuhn’s earlier historiographical work. Overall, the paper concludes that Melogno’s research significantly advanced understanding of Kuhn’s philosophy and deserves to influence future scholarships on Kuhn substantially.